2022
DOI: 10.3390/jcm11051393
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tinnitus on Significant Others

Abstract: Although chronic conditions could cause third-party disability for significant others (SOs), little is known regarding the impact of tinnitus on SO. This study aimed to identify the effects of tinnitus on SOs. SOs of individuals with tinnitus were invited to participate in this study. SOs completed three open-ended questions focusing on the effects of tinnitus. Individuals with tinnitus completed the Tinnitus Functional Index as a self-reported measure of tinnitus severity. A mixed-methods analysis approach wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…This includes significant others in their lives and societal attitudes. Enabling significant others to understand tinnitus and support those with tinnitus and also manage third-party disability may indirectly help those with tinnitus [ 10 ]. Public health campaigns prioritizing awareness of tinnitus and provision of more resources should be aimed for together with interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes significant others in their lives and societal attitudes. Enabling significant others to understand tinnitus and support those with tinnitus and also manage third-party disability may indirectly help those with tinnitus [ 10 ]. Public health campaigns prioritizing awareness of tinnitus and provision of more resources should be aimed for together with interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying where a patient is on this continuum is important in order to adapt the intervention provided accordingly. It has also more recently been highlighted that significant others of those with tinnitus may experience third party disability [ 10 ]. When this is the case, they may not be in a good position to support those with tinnitus.…”
Section: Introductionmentioning
confidence: 99%
“…Depression (PHQ-9) (range 0-27) 7 (5) [0-26] Insomnia (ISI) (range 0-28) 11 (6) [0-27] Health-related quality of life (EQ-5D-5L) (range 0-15) 8 (2) [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Health-related quality of life VAS (EQ-5D-5L VAS) (range 0-100) 76 ( 15…”
Section: Impact Of Tinnitus On the Significant Othersmentioning
confidence: 99%
“…Another study reported that after those with tinnitus saw a professional, it was identified that family members generally had a greater understanding of tinnitus, felt tinnitus had less of an effect on the individual, and that those with tinnitus restricted their activities less often [ 16 ]. More recently, a qualitative study identified that the impact on SOs includes increased responsibility for household duties and childcare and a reduction in the frequency of attending social events, music concerts, and functions [ 17 ]. In some cases, this takes an emotional toll on SOs due to the increased stress and frustration they experience.…”
Section: Introductionmentioning
confidence: 99%